A critical review of numerical methods for the simulation of pultruded fiber-reinforced structural elements. (1st October 2021) - Fascetti, Alessandro; Feo, Luciano; Abbaszadeh, Hadi
Abstract: Pultruded Fiber-Reinforced Polymers (FRP) are innovative structural elements that are experiencing a steady increase in use for different structural applications. Due to their appealing properties that set them apart from traditional construction materials, such as magnetic transparency and excellent strength-to-weight ratio, numerous experimental and numerical studies have been performed in the last decades to assess their performance as structural components. The description of the micro- and macro-scale mechanical features of FRP elements requires multiple levels of information to be accurately characterized to predict their strength, and as a result, researchers have developed computational models with varying levels of complexity to parametrize their response and investigate design parameters through numerical simulations. This paper presents a critical review of the current state-of-the-art in numerical modeling of structural fiber-reinforced polymeric elements for the prediction of their mechanical behavior under serviceability and failure limit state conditions, with particular attention devoted to pultruded Glass Fiber Reinforced Polymers (GFRP), and their use as load-bearing structural elements. The most commonly adopted numerical methods for the solution of this set of problems range from classical Finite Element Method (FEM) approaches to eXtended Finite Element Method (XFEM), Virtual Crack Closure Technique (VCCT), Cohesive Zone Modeling (CZM), Multiscale Reduced Order Modeling (ROM), as well as Random Lattice Modeling (RLM) techniques recently developed by the co-authors. Each one of these methods has its own distinctive features and brings specific challenges and capabilities that will be presented and discussed in detail in the manuscript. This paper, therefore, aims at illustrating the reliability of existing numerical models for the simulation of FRP structural elements and draw conclusions and recommendations for future research, discussing 160 references from the available literature.